Relationships between the femoral neck-preserving ratio and radiologic and clinical outcomes in patients undergoing total-hip arthroplasty with a collum femoris-preserving stem - Liu, Zeming (Medicine (Baltimore), 2019)
The femoral neck-preserving ratio is crucial in arthroplasty with a collum femoris-preserving (CFP) stem. The aim of our study was to analyze the relationships between the neck-preserving ratio and the short-term radiologic and clinical outcomes of patients who underwent total-hip arthroplasty (THA) with a CFP stem. The data of 325 hips from January 2015 to December 2016 were retrospectively reviewed. The demographic and radiologic data before and after surgery were obtained from patients. The neck-preserving ratio was defined as the ratio of the preserved femoral neck length to the preoperative femoral neck length. Correlations between the neck-preserving ratio and the radiologic and clinical outcomes of patients were analyzed. The mean neck-preserving ratio was 66.38 ± 6.91% in the current study. We divided patients into 3 groups according to the neck-preserving ratio: group A (neck-preserving ratio ≤60.00%), group B (60.00% < neck-preserving ratio < 70.00%), group C (neck-preserving ratio ≥70.00%). Radiologic features, including the neck-shaft angle ratio (0.96 ± 0.05), canal fill ratio (0.64 ± 0.07), anterior-posterior offset ratio (1.04 ± 0.10), and lateral offset ratio (2.55 ± 1.56) (ratios of the postoperative values to the preoperative values), and the prevalence of complications was significantly different among the groups (χ(2) = 21.173, P < .001). In the correlation analysis, we found a moderate negative correlation between the neck-preserving ratio and neck-shaft angle ratio (r = −0.308, P < .001) and a slight positive correlation of the neck-preserving ratio with the anterior-posterior offset ratio (r = 0.415, P < .001) and the lateral offset ratio (r = 0.164, P = .003). In the linear regression analyses, the neck-preserving ratio was significantly linearly correlated with the neck-shaft angle ratio (B = −0.232, 95% confidence interval [CI] = −0.311 to −0.154, P < .001), anterior-posterior offset ratio (B = 0.589, 95% CI = 0.447–0.730, P < .001), and lateral offset ratio (B = 3.693, 95% CI = 1.256–6.131, P = .003). However, there was no significant linear correlation between the neck-preserving ratio and the canal fill ratio (B = 0.073, 95% CI = −0.033 to 0.180, P = .174). Logistic regression analyses also showed that a sufficient neck-preserving ratio was a protective factor for periprosthetic femoral fractures (odds ratio [OR] = 0.924, 95% CI = 0.859–0.994, P = .035), dislocations (OR = 0.892, 95% CI = 0.796–0.999, P = .048), and thigh pain (OR = 0.886, 95% CI = 0.818–0.960, P = .003). For CFP stems, an insufficient neck-preserving ratio is significantly correlated with poor radiologic and clinical outcomes. Therefore, surgeons should be cognizant to preserve a sufficient femoral neck length during surgery to improve the outcomes for patients undergoing THA with CFP stems.